Martin's physical pharmacy and pharmaceutical sciences : physical chemical and biopharmaceutical principles in the pharmaceutical sciences - Sinko, Patrick J. (Wolters Kluwer, 2023)
"Consistently revised and updated for more than 60 years to reflect the most current research and practice, Martin's Physical Pharmacy and Pharmaceutical Sciences, 8th Edition, is the original and most comprehensive text available on the physical, chemical, and biological principles that underlie pharmacology and the pharmaceutical sciences. An ideal resource for PharmD and pharmacy students worldwide, teachers, researchers, or industrial pharmaceutical scientists, this 8th Edition has been thoroughly revised, enhanced, and reorganized to provide readers with a clear, consistent learning experience that puts essential principles and concepts in a practical, approachable context. Updated content reflects the latest developments and perspectives across the full spectrum of physical pharmacy and a new full-color design makes it easier than ever to discover, distinguish, and understand information-providing users the most robust support available for applying the elements of biology, physics, and chemistry in work or study. NEW! Enhanced organization clarifies the clinical relevance of content throughout the text and makes learning more efficient for PharmD students. NEW! Full-color design emphasizes essential information and delivers an engaging learning experience. Revised content throughout, including areas such as Molecular Dispersions, Pharmaceutical Micromeritics, Formulation Engineering, Pharmaceutical Biotechnology, and more, provide further clarification and understanding. Abundant examples reinforce how physical chemical and biopharmaceutical principles apply to practice. Key Concept boxes keep students focused on the most important chapter content. "--